Advances in immunology. - Alt, Frederick W., (Advances in immunology ;, 2017)
Advances in Immunology, Volume 135, the latest in a long-established and highly respected publication, presents current developments and comprehensive reviews in immunology. Articles address the wide range of topics that comprise immunology, with this latest update including chapters on GPCR Biology, the Role of Caveolin-1 in BCR and TCR Receptors, New Developments in the Chemokine Field, and The Complement System in Developmental Neurobiology and Neurodegeneration. Readers will find comprehensive information on molecular and cellular activation mechanisms, phylogeny and molecular evolution and clinical modalities. Edited and authored by the foremost scientists in the field, each volume provides up-to-date information and directions for the future.